TINJAUAN YURIDIS PUTUSAN YANG BATAL DEMI HUKUM DIHADAPKAN DENGAN ASAS NE BIS IN IDEM (PUTUSAN NO. 612/PID.B/2023/PN DPS) - Dewi, Putu Putri Pradnyani; Kariyasa, I Made (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2024)
An invalid verdict in favor of an indictment is a judge's ruling that an indictment made by a public prosecutor is less appropriate to file because it does not correspond to the scene and place where the indictment was filed. At this stage, legal counsel has the opportunity to raise objections related to absolute and relative authority in the relevant matter. In this judgment no. 612/Pid.B/2023/PN Dps his indictment was rejected by the court due to his relative authority. The disgrace in this study, namely (1) What factors are the factors of the annulment in favor of the law? (2) How can a judgment declared void by law be appealed if it is associated with the principle of Ne Bis In Idem? The study uses a normative juridical approach. The hokum materials used in this study are based on primary, secondary, and tertiary legal materials. There are two theories used in this study, namely the Theory of the Legal System and the Theory of Authority. In addition to these two theories, there are two principles used, namely the Principle of Legal Certainty and the Principle of Ne Bis In Idem.